THE ROLE OF WOMEN IN THE DEVELOPMENT OF CARPET WEAVING IN THE SURKHAN OASIS (FIRST QUARTER OF THE 21ST CENTURY) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In this article, the activity of the women of the Surkhan oasis related to the development of carpet weaving, which is an ancient type of handicraft industry, and the application of innovations related to the combination of traditionalism and transformational processes in the field are disclosed.